IJTIMOIY-PSIXOLOGIK TADQIQOTLARDA HASAD OB’EKTIGA NISBATAN BERILGAN BAHO - Yu.Baykunusova, G. (SCIENCE and SOCIETY, 2022)
The article presents a socio-psychological classification of envy. In addition, an experimental study of the envious person’s assessment of the object of envy is presented.